Role of base fluid on the thermal conductivity of oleic acid coated magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (COLLOIDS AND SURFACES A-PHYSICOCHEMICAL AND ENGINEERING ASPECTS, 2017)
Thermal conductivity enhancement of nanofluids of oleic acid coated magnetite nanoparticles dispersed in four different base fluids (toluene, xylene, mesitylene, kerosene) is studied to understand the role of the solvent (base fluid). From the correlation of the thermophysical properties of the base fluid with the thermal conductivity of the corresponding nanofluid, it is found that the nanofluid with the base fluid of lower intrinsic thermal conductivity and dielectric constant shows relatively larger enhancement in the thermal conductivity. A linear increase in the thermal conductivity with increasing viscosity is observed for all four nanofluids studied. The concentration dependent thermal conductivity studies showed enhancement only above a particular concentration, within the sensitivity of the measurement, and this critical concentration is different for the different nanofluids. The nanofluid with kerosene showed the lowest critical concentration for thermal conductivity enhancement compared to the other nanofluids. The difference between the experimental thermal conductivity and the calculated value using the Maxwell model is found to depend on the critical concentration. By assuming the critical concentration as the zero concentration, it is found that all the studied nanofluids almost follow the Maxwell model of thermal conductivity. Thus, for the dispersions of the same oleic acid coated magnetite nanoparticles, the base fluid affects the critical concentration for thermal conductivity enhancement, probably due to the interfacial effects arising from the surfactant-solvent interactions.
Keywords: Brownian-Motion; Enhancement; Heat-transfer Characteristics; Magnetic nanofluids; Maxwell model; Nanoparticles; Particle Migration; Size; stability; Suspension; Temprature; Thermal conductivity; Thermophysical properties; transport mechanism; viscosity

Scalable microwave-assisted continuous flow synthesis of CuO nanoparticles and their thermal conductivity applications as nanofluids - Nikam, Arun V.; Dadwal, Arun H. (Advanced Powder Technology, 2019)
We have demonstrated the novel and scalable synthesis of CuO nanoparticles by an integration of microwave and flow synthesis. The shape and size of CuO nanoparticles were tuned by changing the concentration of copper precursor. The production rate of CuO nanoparticles was found to be 5 g/h with 70% conversion of copper acetate into the CuO nanoparticles. The thermal conductivity of CuO nanofluid prepared in ethylene glycol showed linear enhancement with increase in the volume content of CuO nanoparticles produced in batch and flow reactors. (C) 2018 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Flow synthesis; Microwave; Nanofluids; Nanoparticles; scale-up; Thermal conductivity

Review of the recent progress on thermal conductivity of nanofluid - Lenin, Ramanujam; Joy, Pattayil Alias; Bera, Chandan (Journal of Molecular Liquids, 2021)
Thermal properties of nanofluids are very well investigated by the global research community for their various applications. The dispersion and stability of the nanoparticles in the base fluid are the essential requirements for the efficient utilization of nanofluids in many applications. The interfacial layer plays a crucial role in the dispersion, stability, and heat transfer properties of the nanofluid. The heat transfer property of the nanofluids is mainly influenced by the heat transfer properties at the particle-fluid interface. The thickness and thermal conductivity of the interfacial layer are the crucial factors that decide the heat transfer at the interface, and the difficulties in the determination of these factors limits the progress of the research. In this review article, the experimental studies on the thickness and thermal conductivity of the interfacial layer are reviewed briefly. The effect of interfacial the layer on the nanoscale mechanisms and thermophysical properties of nanofluids are reviewed. The effect of various tunable parameters on the heat transfer properties of the interfacial layer is also reviewed. This review will be beneficial for fine-tuning nanofluid's thermal properties and their commercial applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Interfacial layer; Interfacial thermal conductance; Nanofluid; Surfactants; Thermal conductivity